2021
DOI: 10.1021/acsnano.1c00990
|View full text |Cite
|
Sign up to set email alerts
|

Niobium and Titanium Carbides (MXenes) as Superior Photothermal Supports for CO2 Photocatalysis

Abstract: The conversion of CO2 into fuels and feedstock chemicals via photothermal catalysis holds promise for efficient solar energy utilization to tackle the global energy shortage and climate change. Despite recent advances, it is of emerging interest to explore promising materials with excellent photothermal properties to boost the performance of photothermal CO2 catalysis. Here, we report the discovery of MXene materials as superior photothermal supports for metal nanoparticles. As a proof-of-concept study, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(106 citation statements)
references
References 70 publications
0
106
0
Order By: Relevance
“…Under 300 W Xe light with an intensity of 36 suns, the Ni/Nb 2 C catalyst achieved the highest CO 2 conversion rate of 8.5 mol g −1 h −1 . 190 Therefore, this study successfully Table 1. continued bridges the gap between photothermal CO 2 methanation and photothermal MXene materials toward more efficient solar-tochemical energy conversion.…”
Section: Mxene As a Co-catalyst For Co 2 Methanationmentioning
confidence: 87%
“…Under 300 W Xe light with an intensity of 36 suns, the Ni/Nb 2 C catalyst achieved the highest CO 2 conversion rate of 8.5 mol g −1 h −1 . 190 Therefore, this study successfully Table 1. continued bridges the gap between photothermal CO 2 methanation and photothermal MXene materials toward more efficient solar-tochemical energy conversion.…”
Section: Mxene As a Co-catalyst For Co 2 Methanationmentioning
confidence: 87%
“…Recently, a new two-dimensional (2D) layered transition-metal carbide/carbonitride/nitride family, MXenes, entered the vision of chemists in many scientific fields, such as energy storage and conversion, electromagnetic wave absorption and shielding, , sensing, and photocatalysis. In the field of photocatalysis for H 2 production, Ti 3 C 2 is one of the most extensively studied MXenes because (1) the good hydrophilic ability is favorable for the reactions occurring in the aqueous environment, (2) the good electrical conductivity favors the separation and transfer of photoinduced charge carriers from semiconductors, , and (3) the appropriate work function enables it to form a Schottky heterojunction with most semiconductors. , In addition, diversiform types of Ti 3 C 2 including quantum dots (QDs), accordion-like multilayers, and single- or few-layered ultrathin nanosheets (NSs) further extended its scope of application. Pioneering work has been done by Ran et al, where the Ti 3 C 2 QDs were verified to be an effective cocatalyst of CdS for photocatalytic H 2 production under visible-light irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies found that the light‐absorption ability can be enhanced by increasing the loading amount of metal nanoparticles [4–5] . We recently reported that MXene materials could serve as light absorptive supports to boost photothermal catalytic performance [6] . Other researchers have also developed strategies to manipulate light by designing structured catalysts.…”
Section: Figurementioning
confidence: 99%